Effects of dietary supplementation with dandelion tannins or soybean isoflavones on growth performance, antioxidant function, intestinal morphology, and microbiota composition in Wenchang chickens - Li, Xiang; Sun, Ruiping; Liu, Quanwei; Gong, Yuanfang; Ou, Yangkun; Qi, Qi; Xie, Yali; Wang, Xiuping; Hu, Chenjun; Jiang, Shouqun; Zhao, Guiping; Wei, Limin (Frontiers in Veterinary Science, 2023)
Many benefits have been found in supplementing tannins or soybean isoflavones to poultry, including increased body weight gain, antioxidant activity, and better intestinal morphology. However, few studies tested the influence of dandelion tannins or soybean isoflavones supplementation on Wenchang chickens. This study investigates the effects of dietary supplementation with dandelion tannins or soybean isoflavones on the growth performance, antioxidant function, and intestinal health of female Wenchang chickens. A total of 300 chickens were randomly divided into five groups, with six replicates per group and 10 broilers per replicate. The chickens in the control group (Con) were fed a basal diet; the four experimental groups were fed a basal diet with different supplements: 300 mg/kg of dandelion tannin (DT1), 500 mg/kg of dandelion tannin (DT2), 300 mg/kg of soybean isoflavone (SI1), or 500 mg/kg of soybean isoflavone (SI2). The experiment lasted 40 days. The results showed that the final body weight (BW) and average daily gain (ADG) were higher in the DT2 and SI1 groups than in the Con group (P < 0.05). In addition, dietary supplementation with dandelion tannin or soybean isoflavone increased the level of serum albumin (P <0.05); the concentrations of serum aspartate aminotransferase and glucose were significantly higher in the SI1 group (P < 0.05) than in the Con group and the concentration of triglycerides in the DT1 group (P < 0.05). The serum catalase (CAT) level was higher in the DT1 and SI1 groups than in the Con group (P < 0.05). The ileum pH value was lower in the DT2 or SI1 group than in the Con group (P < 0.05). The jejunum villus height and mucosal muscularis thickness were increased in the DT2 and SI1 groups (P < 0.05), whereas the jejunum crypt depth was decreased in the DT1 or DT2 group compared to the Con group (P < 0.05). In addition, the messenger RNA (mRNA) expression level of zonula occludens 1 (ZO-1) in the duodenum of the SI1 group and those of occludin, ZO-1, and claudin-1 in the ileum of the DT2 and SI1 groups were upregulated (P < 0.05) compared to the Con group. Moreover, the DT2 and SI1 groups exhibited reduced intestinal microbiota diversity relative to the Con group, as evidenced by decreased Simpson and Shannon indexes. Compared to the Con group, the relative abundance of Proteobacteria was lower and that of Barnesiella was higher in the DT2 group (P < 0.05). Overall, dietary supplementation with 500 mg/kg of dandelion tannin or 300 mg/kg of soybean isoflavone improved the growth performance, serum biochemical indexes, antioxidant function, and intestinal morphology and modulated the cecal microbiota composition of Wenchang chickens.